The Role and Importance of the Organization of Educational Projects in the Teaching of Natural Sciences in General Education Schools - Koychiyeva, Zarnigorkhan Abdmannab qizi (Peerian Journals Publishing, 2022)
The article discusses the methodology of organizing educational projects, which is one of the most optimal ways to develop personal intellectual and creative abilities of students in the teaching of natural sciences in secondary schools.
Keywords: Project work; research projects; express projects; types of projects